2004
DOI: 10.1038/sj.sc.3101653
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 4-aminopyridine on gait in ambulatory spinal cord injuries: a double-blind, placebo-controlled, crossover trial

Abstract: Animal and human research have shown that the drug 4-aminopyridine (4-AP) may improve gait in spinal cord lesions by enhancing nerve transmission to affected muscles. Study design: Prospective, randomized, double-blind, placebo-controlled, crossover trial. Objectives: To determine the efficacy of 4-AP in improving lower limb muscle strength and biomechanical gait patterns of chronic spinal cord injuries (SCI). Setting: The Rehabilitation Centre (Ottawa, Canada). Methods: In all, 15 chronic, ambulatory SCI pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 27 publications
1
38
0
Order By: Relevance
“…Hematologic effects include thrombocytopenia. Posterior tibial artery vasospasm was discussed in one case and was successfully treated with oral nifedipine [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hematologic effects include thrombocytopenia. Posterior tibial artery vasospasm was discussed in one case and was successfully treated with oral nifedipine [20].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, research regarding its efficacy in SCI has been inconclusive. Although animal models and some early studies reported improvement in function and sensation, subsequent randomized, placebo-controlled studies have not demonstrated clinically significant benefits [16][17][18][19][20][21][22]. Summative interpretation of these results is difficult due to small numbers, mixed patient populations and variations in duration, dosage, and mechanism of administration.…”
Section: Introductionmentioning
confidence: 99%
“…One theory is that improvement results from blockage of potassium channels exposed on demyelinated, intact axons. However, 4-AP also potentiates synaptic transmission and skeletal muscle twitch tension (Smith et al, 2000) and human clinical trials of 4-AP in chronic SCI have been inconclusive so far where some report modest and temporary improvement on motor and sensory functions especially reduction in spasticity, whereas others do not find significant beneficial effects (Potter et al, 1998;van der Bruggen et al, 2001;Wolfe et al, 2001;DeForge et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Literature shows that there are no benefits from the drugs Levodopa [35,42] and 4-Aminopyridine [43,44].…”
Section: Pharmacologymentioning
confidence: 99%